A dessubjetivação da interpretação jurídica a partir da hermenêutica filosófica: a tradição como fundamento ontológico - Daniel Carreiro Miranda (2020)
This thesis is dedicated to the investigation of the possibility of formulating an ontological foundation for legal interpretation, based on tradition, a notion extracted from the philosophical hermeneutic thinking of Hans-Georg Gadamer. In this sense, our collateral purpose is to clarify the concept of legal hermeneutic situation, and the intersubjective structuring of the legal hermeneutic phenomenon, from an experiential notion of understanding as a way of being that constitutes the breadth of the world of historical life and can be understood in the context of context of the factual intentional experiences intersubjectively in order to find the appropriate meaning for the Law, which in our case, is restricted only to the ontological question of legal interpretation. The guiding thread of the thesis runs through the need to no subjectivation the legal interpretation, because any formalization of the self will inevitably lead us to metaphysical structures, or to structures that ignore or lessen our temporal condition in the world. From the legal hermeneutic rationality, whose foundation is through tradition. We start from the assumption that legal interpretation is not an action that consists in the subject's apprehension of the object, because knowing necessarily transcends the subject and its relation to the object; legal knowledge is not the exclusive result of the creation of the subject who places or supposes certain conditions in order for him to understand. In this sense, the interpretable guides the interpretation, in the phenomenological relationship that is established between both. Therefore, there is a need to counter the interpretive legal horizon from the subjective sphere, significantly accentuated by the instrumentalist currents of language and interpretation, in order to highlight the philosophical hermeneutical thinking in Law.